Frequency of Hepatitis C in Patients with Diabetes Mellitus - Sara Shamshad Ali, Muhammad Ramiz, Almas Sarwar, Rubab Munawar, Adnan Ali, Madiha Akram (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The purpose of this study is to determine the prevalence of hepatitis C infection among patients of diabetes mellitus. Study Design: Cross-sectional/descriptive study Place and Duration: The study was conducted at Medicine department of Benazir Bhutto Hospital, Rawalpindi and Avicenna Teaching Hospital, Lahore during the period from July 2021 to December 2021. Methods: There were 130 patients of both genders had diabetes mellitus were presented in this study. Patients were aged between 25-70 years. Data on the recruited patients’ age, gender, BMI, residence, and educational attainment were collected after informed written permission was obtained. Prevalence of hepatitis infection C was recorded by using ELISA (Enzyme Linked Immuno-Sorbent Assay) method. SPSS 24.0 was used to analyze complete data. Results: Among 130 patients of diabetes, 70 (53.8%) were females and 60 (46.2%) were males. Mean age of the patients was 39.45±15.74 years and had mean BMI 25.8±7.41 kg/m2. We found that majority of the cases were from rural areas 80 (61.5%) and 50 (38.5%) had urban residency. 58 (44.6%) patients were educated and 72 (55.4%) patients were uneducated. Frequency of hepatitis C was found among 40 (30.8%) patients. All patients of HCV had diabetes mellitus II and most the patients were females 25 (62.5%). Most of the patients 22 (55%) had glycemic value 180 mg/dl range. Among 40 cases of HCV 10 (25%) were aged between 25-35 years, 22 (55%) were aged between 36-45 years and 8 (20%) had ages >45 years. Increased level of Serum Glutamic -Pyruvic Transaminase (SGPT) was found in 32 (80%) patients. Conclusion: We concluded in this study that the frequency of HCV infection was found among 30.8% patients most probably found among cases of diabetes mellitus II.